Short-Duration, Pulsatile, Electrical Stimulation Therapy Accelerates Axon Regeneration and Recovery following Tibial Nerve Injury and Repair in Rats. Issue 4 (3rd February 2022) - Roh, Joseph; Schellhardt, Lauren; Keane, Grace C.; Hunter, Daniel A.; Moore, Amy M.; Snyder-Warwick, Alison K.; Mackinnon, Susan E.; Wood, Matthew D.
Abstract : Background: Repair of nerve injuries can fail to achieve adequate functional recovery. Electrical stimulation applied at the time of nerve repair can accelerate axon regeneration, which may improve the likelihood of recovery. However, widespread use of electrical stimulation may be limited by treatment protocols that increase operative time and complexity. This study evaluated whether a short-duration electrical stimulation protocol (10 minutes) was efficacious to enhance regeneration following nerve repair using rat models. Methods: Lewis and Thy1–green fluorescent protein rats were randomized to three groups: 0 minutes of electrical stimulation (no electrical stimulation; control), 10 minutes of electrical stimulation, and 60 minutes of electrical stimulation. All groups underwent tibial nerve transection and repair. In the intervention groups, electrical stimulation was delivered after nerve repair. Outcomes were assessed using immunohistochemistry, histology, and serial walking track analysis. Results: Two weeks after nerve repair, Thy1–green fluorescent protein rats demonstrated increased green fluorescent protein–positive axon outgrowth from the repair site with electrical stimulation compared to no electrical stimulation. Serial measurement of walking tracks after nerve repair revealed recovery was achieved more rapidly in both electrical stimulation groups as compared to no electrical stimulation. Histologic analysis of nerve distal to the repair at 8 weeks revealed robust axon regeneration in all groups. Conclusions: As little as 10 minutes of intraoperative electrical stimulation therapy increased early axon regeneration and facilitated functional recovery following nerve transection with repair. Also, as early axon outgrowth increased following electrical stimulation with nerve repair, these findings suggest electrical stimulation facilitated recovery because of earlier axon growth across the suture-repaired site into the distal nerve to reach end-organ targets. Clinical Relevance Statement: Brief (10-minute) electrical stimulation therapy can provide similar benefits to the 60-minute protocol in an acute sciatic nerve transection/repair rat model and merit further studies, as they represent a translational advantage.